Analisis Kebangkrutan PT. Prasidha Aneka Niaga Tbk Menggunakan Metode Altman Z-Score Periode 2016 - 2020 - Husein, Difiana; Febryari Anit, Widya (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
Bankruptcy analysis by PT. Prasidha Aneka Niaga Tbk 2016-2020 uses the Altman Z-Score method. The purpose of this research is to find out whether a company is experiencing bankruptcy in the current period so that corrective actions can be taken at an early stage. This study used a quantitative descriptive method and documents for data collection. He gathered data from company records after what was needed to explain the research questions. The analytical method used is the Altman Z-Score method. According to the survey results, the company's financial ratios achieved from 2016 to 2020 have increased in 2017 and 2018 after experiencing financial difficulties in 2016, this indicates that it is not experiencing financial difficulties but is in a stable condition. However, in 2019 and 2020, it will once again face financial difficulties.